Ontogenia e Genética de Flores Casmógamas e Cleistógamas de Utricularia triloba Benj. (Lentibulariaceae) - Carvalho, Samanta Gabriela Medeiros [UNESP] (2022)
ABSTRACT – The Utricularia genus is the largest within the Lentibulariaceae family, presenting high morphological diversity, both for vegetative and reproductive structures. This diversity may be related to the ability to conquer and adapt to new habitats, including variations in reproduction strategies. Floral plasticity can also be found in some Utricularia species, including floral dimorphism, with the production of two distinct types of flowers, chasmogamous (CH) and cleistogamous (CL). CH flowers are related to the pollinators’ attraction and consequently to cross-pollination, while CL flowers present floral organs close and isolated from the external environment, favoring self-pollination. In Utricularia, there are reported at least 12 species with cleistogamous flowers, including U. triloba, however, only two comparative morphologic studies covered this type of flower. Regarding the genetic approach there are no reports of studies about identification and evolution of floral ontogenesis genes in the Lentibulariaceae family. In this sense, herein we described and compared the CH and CL flowers micromorphology of U. triloba, as well as identified and analyzed the ARF and MADS-box gene families, which have members with related functions to the formation of the main floral organs affected by cleistogamy, such as petals, pistils and stamens. The histologic and microscopic analyses revealed consistent characters that have been reported for CA flowers, and showed important differences in CL Flowers, including the absence of glandular trichomes and differences on corolla epidermis of CL flowers. The identification and evolutionary analyses for the gene families showed subfamilies expansions and contractions of the ARF and MADS-box genes that may be related to the U. triloba adaptation to different environmental pressures, as well as to the flower development and formation, and to the mechanisms that define the mixed mating system found in natural populations of this species.